Chemical interactions between silver nanoparticles and thiols: a comparison of mercaptohexanol against cysteine - Toh, H; Batchelor-McAuley, C; Tschulik, K; Compton, R (Science China Press, 2014)
The interaction between citrate capped silver nanoparticles and two different thiols, mercaptohexanol (MH) and cysteine, was investigated. The thiols interacted with silver nanoparticles in a significantly contrasting manner. With MH, a sparingly soluble silver(I) thiolate complex AgSRm (Rm = -(CH2)6OH) was formed on the silver nanoparticle surface. Cyclic voltammograms and UV-vis spectra were used to infer that the AgSRm complex on the nanoparticle surface undergoes a phase transition to give a mixture of AgSRm and Ag2S-like complexes. In contrast, when silver nanoparticles were exposed to cysteine, the citrate capping agent on the silver nanoparticles was replaced by cysteine to give cysteine capped nanoparticles. As cysteine capped nanoparticles form, the electrochemical data displayed a decrease in oxidative peak charge but the UV-vis spectra showed a constant signal. Therefore, cysteine capped nanoparticles were suggested to have either inactivated the silver surface or else promoted detachment from the electrode surface. © 2014 Science China Press and Springer-Verlag Berlin Heidelberg.